A formative evaluation of a systemic infant mental health program designed to treat infants and their families through a rural community mental health center - Schliep, Corey Dale (Kansas State University, 2008)
Despite the intensified research efforts into the field of Infant Mental Health and Marriage and Family Therapy, a truly systemically designed program has not been developed. This formative evaluation study illuminates the design phase, its developmental process, and the professional staff member’s experience of this newly implemented “Options” program. I focused specifically on Crawford County Community Mental Health Center’s innovative systemic approach to issues related to infant mental health. In this body of work, I describe the process of creating this innovative approach, identified how the program originators made decisions about their approach and how the approach is being operationalized on a daily basis by interviewing the clinicians, who are providing the services and the administrators who created and oversee the program. I utilized a qualitative approach in the design, transcription categorization, and data analysis. This formative evaluation used the “flashback approach” to tell the story of the evaluation findings, this included an Executive Summary. This study’s exploration yielded a clearer understanding of the developmental process of the infant mental health program and its initial implementation. The results of this evaluation revealed that there are a number of core program components (three levels of focus: child and family, program, and community and catchment area) that were organized and clearly disseminated throughout the staff. The interviews revealed that the program has encountered problematic issues including; policy and procedural agreements and mandates, staff turnover, program ownership and funding limitations. It grew increasingly clear that the value of the program’s positive impact on families outweighed the perceived hassle of establishing and implementing the program. This evaluation produced a number of program recommendations for program perpetuation and potential improvements. The program recommendations addressed the challenges facing the “Options Program” are explained. The future research implications of this formative evaluation are enumerated.
Keywords: Infant Mental Health; Community Mental Health Center; Marriage and Family Therapy; Health Sciences, Mental Health (0347); Health Sciences, Public Health (0573); Psychology, Developmental (0620)